E-participation as a possible upgrading of representative democracy - Gaber, Slavko (Teorija in praksa, 2014)
After less than 120 years of fully fledged representative democracy, and with the crisis and possibly even the dead end of the existing way of production, questioning the future of democracy is back again. It is claimed that direct democracy may be the next step of the development of the political system. The present article considers a less ambitious project, presenting a possible upgrading of representative democracy in Slovenia, a country with a short history of functioning representative democracy and with the experience of an experiment in direct democracy, which collapsed together with the Socialist Republic of Yugoslavia. The article presents a model that should enable the widening of democratic participation in decision making, and discusses the possible engagement of increasingly educated civil society in political deliberation, making use of the internet and new media. The proposed Slovenian model of junctures of democracy emerged after intensive and prolonged discussion within the so-called "Free University" that emerged after public protests in 2013. As an example of good practice enabling reflection on the possible upgrading of representative democracy in Slovenia, we refer to the Finnish practice of e-democracy at the local level (in particular the Tampere case) and at the state level.
Keywords: democracy; demokracija; e-demokracija; neposredna demokracija; predstavniška demokracija; Slovenia; Slovenija